Automated entry technologies for confined space work activities: A survey. Issue 4 (3rd April 2017) - Botti, Lucia; Ferrari, Emilio; Mora, Cristina
ABSTRACT: Work in confined spaces poses a significant risk to workers and rescuers involved in the emergency response when an accident occurs. Despite several standards and regulations define the safety requirements for such activities, injuries, and fatalities still occur. Furthermore, the on-site inspections after accidents often reveal that both employers and employees fail to implement safe entry procedures. Removing the risk is possible by avoiding the worker entry, but many activities require the presence of the operator inside the confined space to perform manual tasks. The following study investigates the available technologies for hazardous confined space work activities, e.g., cleaning, inspecting, and maintenance tasks. The aim is to provide a systematic review of the automated solutions for high-risk activities in confined spaces, considering the non-man entry as the most effective confined space safety strategy. Second, this survey aims to provide suggestions for future research addressing the design of new technologies. The survey consists of about 60 papers concerning innovative technologies for confined space work activities. The document review shows that several solutions have been developed and automation can replace the workers for a limited number of hazardous tasks. Several activities still require the manual intervention due to the complex characteristics of confined spaces, e.g., to remove the remains of the automatic cleaning process from the bottom of a tank. The results show that available technologies require more flexibility to adapt to such occupational environments and further research is needed.